Age-matched versus non-age-matched comparison of clinical and functional differences between delusional disorder and schizophrenia: a systematic review - Hui, Christy Lai Ming; Chiu, Tsz Ching; Chan, Evie Wai Ting; Hui, Priscilla Wing Man; Tao, Tiffany Junchen; Suen, Yi Nam; Chan, Sherry Kit Wa; Chang, Wing Chung; Lee, Edwin Ho Ming; Chen, Eric Yu Hai (Frontiers in Psychiatry, 2023)
Background It has been widely suggested that delusional disorder (DD) differs from schizophrenia (SZ). However, whether the two disorders are truly distinct from each other is inconclusive as an older age of onset is closely linked to a better prognosis in psychotic disorders. In order to delineate the potential influence of age on outcomes, we undertook a systematic review on the clinical and functional differences between DD and SZ in age-matched and non-age-matched cohorts. Methods Electronic databases were retrieved up to May 2022. Included studies were analyzed with reference to statements about clinical, cognitive and functional differences between DD and SZ. Results Data synthesized from 8 studies showed (1) extensive effects of age on positive, general psychopathological symptoms and functioning, but (2) consistent differences between the two disorders in terms of negative symptoms and hospitalizations regardless of age matching. Conclusion There is currently insufficient evidence to conclude whether DD is completely distinct from SZ, but our review showed support for the confounding effect of age in comparisons of psychotic disorders with different ages of onset. Future studies shall take note of other possible confounding variables, methods of age-matching and the importance of longitudinal information in deducing whether the two disorders differ from each other in course and outcome.